Exercise and sport pharmacology - Mamrack, Mark D. (New York, NY : Routledge, 2021)
"Exercise and Sport Pharmacology is an essential book for teaching upper-level undergraduates or entry-level graduate students about how drugs can affect exercise and how exercise can affect the action of drugs. It leads students through the related pathology, exercise physiology, and drug action of many of todays chronically used medications and discusses how drugs can affect exercise performance. This new second edition of the book is divided into four parts. Part I provides the basics of pharmacology, exercise physiology, autonomic pharmacology, and the stress response; Part II presents chapters on major cardiovascular and respiratory drug classes; Part III describes frequently prescribed medications for such common conditions as diabetes, depression, pain, fever, inflammation, and obesity; and Part IV includes discussions of nutritional supplements and commonly used drugs such as caffeine, nicotine, cannabis, and performance-enhancing drugs. The second edition has many updates, enhances muscle cell physiology, includes the involvement of the gut microbiome, and each chapter has a new section on the effects of aging. In Parts II and III, chapters include an overview of the pathology therapeutic drugs are designed to treat and how the drug works in the human body. In contrast to standard pharmacology texts, Exercise and Sport Pharmacology also includes the effect of exercise on the pathology of the condition and the effect of exercise on how the body responds to a drug. Part IV is concerned with self-medication and drugs or supplements taken without a prescription or with limited medical supervision. Throughout, figures and tables as well as data from experiments in exercise pharmacology help to illustrate and summarize content. Each chapter opens with an on-going case example to preview and apply chapter content. In the text, boldface terms indicate which concepts are contained in the book's Glossary. Chapters conclude with a Key Concepts Review and Review Questions"--
OCLC-licensed vendor bibliographic record.
Keywords: Exercise -- Physiological aspects; Drugs -- Physiological effect; Doping in sports; Sports -- Physiological aspects; MEDICAL / Sports Medicine; MEDICAL / Physiology; MEDICAL / Drug Guides